Measuring a scientifically multifaceted concept: The jungle of organizational legitimacy - Francisco Díez-Martín; Alicia Blanco-González; Emilio P. Diéz de Castro (European Research on Management and Business Economics (ERMBE), 2021)
Measuring organizational legitimacy has become a challenge for researchers because they face a mul-tilevel construct, where diverse terminologies, approaches, and evaluators converge. As a consequence,researchers have developed different conceptual proposals that have, in turn, given rise to multiple mea-surement methodologies, generating some uncertainty among researchers about the best measurementinstrument. These methodologies are not generalizable to other contexts, do not integrate the differentapproaches to assessing legitimacy, nor do they explain their suitability for specific contexts. This paperproposes a general process for measuring organizational legitimacy in any context and across differ-ent terminologies, while providing criteria for a justified choice of measurement instrument. The studydifferentiates between organizational legitimacy measurements based on perceptions and secondarydata, as well as between legitimacy as a global or as a dimensions-based judgment. We also present abroader typology of legitimacy dimensions that includes diverse fields of knowledge, avoids overlappingdimensions, and provides concept definitions in order to facilitate understanding by researchers andmanagers.
Keywords: M1; M21; 650; Organizational legitimacy; Legitimacy measurement; Legitimacy dimensions; Judgment